Anterior Chest Wall Reconstruction Using Polypropylene Mesh: A Retrospective Study - Schroeder-Finckh, Alexander; Lopez-Pastorini, Alberto; Galetin, Thomas; Defosse, Jerome; Stoelben, Erich; Koryllos, Aris (The Thoracic and Cardiovascular Surgeon, 2020)
Background Anterior chest wall resection for oncological purposes is usually combined with a form of reconstruction. Most surgeons are convinced that ventrally located defects more than 4 to 5 cm require adequate reconstruction to minimize the risk of lung herniation and respiratory distress through paradox motion. We describe our in-house results of ventral chest wall reconstruction using polypropylene mesh without the use of metallic or biological implants regardless of the extent of chest wall resection.Methods Patient selection involved ventral chest wall resection and reconstruction by polypropylene mesh for all indications such as primary tumors, metastasis, or infiltration by lung cancer from January 2008 to December 2016. Primary end point was the difference between both sides. Secondary end points were postoperative complications such as infection, surgical revision, and pulmonary complications.Results Forty-five cases of isolated anterior reconstruction could be identified. In 34 cases, postoperative computed tomography scan of the thorax was available. Fifteen males and 19 females with a median age of 70.5 years were operated. The evaluation of maximum hemithorax diameter between operated and nonoperated sides was documented in centimeters, and the difference was documented in percentage. The mean percentage difference was 11.1% (minimum: 0.3, maximum: 44.4). In one case, wound infection with positive culture could not be treated conservatively and required operative revision and removal of the polypropylene mesh.Conclusion Polypropylene mesh, though not rigid, can safely be used for anterior chest wall reconstruction.
Keywords: chest; chest wall; sternum; surgery; complications